Hepatopancreatoduodenectomy –a controversial treatment for bile duct and gallbladder cancer from a European perspective. Issue 9 (September 2020) - D'Souza, Melroy A.; Valdimarsson, Valentinus T.; Campagnaro, Tommaso; Cauchy, Francois; Chatzizacharias, Nikolaos A.; D'Hondt, Mathieu; Dasari, Bobby; Ferrero, Alessandro; Franken, Lotte C.; Fusai, Giuseppe; Guglielmi, Alfredo; Hagendoorn, Jeroen; et al.
Abstract: Background: Hepatopancreatoduodenectomy (HPD) is an aggressive operation for treatment of advanced bile duct and gallbladder cancer associated with high perioperative morbidity and mortality, and uncertain oncological benefit in terms of survival. Few reports on HPD from Western centers exist. The purpose of this study was to evaluate safety and efficacy for HPD in European centers. Method: Members of the European-African HepatoPancreatoBiliary Association were invited to report all consecutive patients operated with HPD for bile duct or gallbladder cancer between January 2003 and January 2018. The patient and tumor characteristics, perioperative and survival outcomes were analyzed. Results: In total, 66 patients from 19 European centers were included in the analysis. 90-day mortality rate was 17% and 13% for bile duct and gallbladder cancer respectively. All factors predictive of perioperative mortality were patient and disease-specific. The three-year overall survival excluding 90-day mortality was 80% for bile duct and 30% for gallbladder cancer (P = 0.013). In multivariable analysis R0-resection had a significant impact on overall survival. Conclusion: HPD, although being associated with substantial perioperative mortality, can offer a survival benefit in patient subgroups with bile duct cancer and gallbladder cancer. To achieve negative resection margins is paramount for an improved survival outcome.